INTRODUKSI DAUN KERING LEGUMINOSA POHON SEBAGAI SUMBER PROTEIN DALAM PAKAN-KOMPLIT UNTUK TERNAK DOMBA DARA - Ulin Nuschati; Budi Utomo; Susanto Prawirodigdo (Caraka Tani: Journal of Sustainable Agriculture, 2010)
An experiment was conducted to evaluate the effect of formulated complete feed containing either one of dried legume leave of leucaena (Diet1), gliricidia (Diet2), or calliandra (Diet3) for protein sources of feed on the reproduction performance of the thin tailed ewes. The experiment used 18 head of ewe lambs of about 8 months old, which were individually penned in an elevated barn belongs to The Central Java Assessment Institute for Agricultural Technology, Ungaran. Each experimental animal was randomly fed either one of the three experimental diets. In addition, the study also employed 3 bucks of the fat tailed sheep for mating the ewes. Measurements were made for dry matter (DM) consumption of feed, weight gain, first oestrus occurrence, body weight at first oestrus, and pregnancy rate of the ewes. Results showed that the ewes fed Diet 2 consumed (535.7 g DM/d) larger (P<0.05) amount of feed than that receiving Diet 1 (489.7 g DM/d) or either Diet 3 (500.3g DM/d). The data exhibited that palatability of Diet2 was superior among the three experimental diets. Consistently, weight gain of ewes (37.4 g/d) and the body weight at the first oestrous occurred (17.88 kg) of ewe fed gliricidia diet (Diet2) also higher (P<0.05) than that consuming Diet1 (21 g/d and 15.88 kg) or the one consumed Diet3 (20.4 g/d and 16.37 kg). However, the distinction effect of various dried legume three leaves inclusion in the diets on the pregnancy rate was not significant (66.7% versus 66.7% versus 60%, for the animals fed Diet1 versus Diet2 versus Diet3). Overall, the present study concluded that the use of dried legume three leaves for protein sources in the complete feeds for ewes did not exhibit any negative effect.